2019
DOI: 10.1371/journal.pone.0216239
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and complications of perioperative atrial fibrillation after non-cardiac surgery for malignancy

Abstract: Background Perioperative atrial fibrillation (POAF) is one of the common arrhythmias in the setting of non-cardiac surgeries for malignancy. As POAF may cause subsequent adverse events, it is important to confirm its characteristics and risk factors. Materials and methods The pr osp e ctive cohort stu d y of surve i llan c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
(20 reference statements)
0
18
0
1
Order By: Relevance
“…AF can precede or follow the development of other cardiac and noncardiac complications after noncardiac surgery in high-risk patients, such as those undergoing surgery for malignancy. 22…”
Section: Discussionmentioning
confidence: 99%
“…AF can precede or follow the development of other cardiac and noncardiac complications after noncardiac surgery in high-risk patients, such as those undergoing surgery for malignancy. 22…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AF is associated with significantly higher occurrence of perioperative complications in various surgical operations, including urinary system surgery, liver transplantation, etc. (6,7,25).…”
Section: Discussionmentioning
confidence: 99%
“…ECG monitoring for 48–72 h is guideline recommended for detection of postoperative AF after thoracic surgery [24] . However, surveillance for AF is not routine after non-cardiothoracic surgery, nor during many acute medical illnesses, and thus considerable numbers of transient secondary AF episodes will go undetected, particularly when a high proportion are asymptomatic or subclinical [25] , [26] . Further work is required to clarify the true incidence of secondary AF, and if necessary, develop strategies to better detect these during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%